2016
DOI: 10.1186/s13033-016-0105-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatic problems among medical students: a myth or reality?

Abstract: BackgroundMedical students are exposed to stress and this can predispose them to psychological and behavioral consequences.MethodsPsychosomatic disorders were investigated among 385 medical students from two teaching hospitals using a stratified random sampling. The Enugu somatization Scale (ESS) was used to evaluate for presence of somatization in the participants. Statistical analysis was done with the Statistical Package for Social Sciences (SPPS) version 19 (Chicago IL).ResultsA total of 385 medical studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Six of the seven included studies reported separate hypochondriasis prevalence rates for male and female health science students; females had a higher rate than males, but the difference was not significant. Chinawa [28] and Puthran [37] confirmed that female medical students did not present a higher morbidity of psychosomatic problems than male medical students. In China, female college students now enjoy the same rights to education, share the same curricula, experience the same pressures, and play equally active roles in school and social competition as their male counterparts [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six of the seven included studies reported separate hypochondriasis prevalence rates for male and female health science students; females had a higher rate than males, but the difference was not significant. Chinawa [28] and Puthran [37] confirmed that female medical students did not present a higher morbidity of psychosomatic problems than male medical students. In China, female college students now enjoy the same rights to education, share the same curricula, experience the same pressures, and play equally active roles in school and social competition as their male counterparts [38].…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have shown that health science students have more easy access to medical resources and do not avoid seeking medical care when suffering pain or potential dysfunction [9,26], some researchers have found that they do not seek reassurance more frequently than non-health-science students [4,6,27]. Their perceptions of the medical profession [28] and the time required to receive medical services [29] influence students’ healthcare-seeking behaviors. With these findings in mind, whether health science students seek medical services when they have hypochondriac symptoms remains unclear, and it is worthwhile to explore what contributes to the inconsistency.…”
Section: Introductionmentioning
confidence: 99%
“… 53 For instance, because the concept of a stress response has clear affinities with anxiety 53 stress can predispose patients to psychological and behavioral consequences. 63 Stress may be acute, episodic acute, and chronic as well as physical and/or emotional. For instance, stress may be due to the pressures of time, and/or be anticipatory (foreboding) and/or be situational such as stress associated with encountering people.…”
Section: Stressmentioning
confidence: 99%
“…The link between stress and impaired health can be monitored, in such cases, as the disease appears, develops, or recurs. Psychosomatic disorders have been attributed to inadequate activation of the autonomic nervous system, endocrine and immune systems (Chinawa, Nwokocha, Manyike, Chinawa, Aniwada, & Ndukuba, 2016). Most commonly reported symptomatology in the literature has physical, emotional, and behavioral association.…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms are usually found in systems that are not under the voluntary control of the nervous system, for example, diarrhea, sweating and palpitations, and are therefore part of the activity of the autonomic nervous system (Charis, 2018). Chinawa and coworkers examined the association of psychosomatic disorders with poor school performance in medical students and obtained a significant association (Chinawa et al, 2016). Most studies to date have shown that children and adolescents who use active coping strategies to reduce the discomfort caused by a stressful event experience significantly fewer psychosomatic symptoms compared to children who passively accept the situation (Vulić-Prtorić & Cifrek-Kolarić, 2011).…”
Section: Introductionmentioning
confidence: 99%